2011
DOI: 10.1017/s1466252311000193
|View full text |Cite
|
Sign up to set email alerts
|

Detection of O antigens inEscherichia coli

Abstract: Lipopolysaccharide on the surface of Escherichia coli constitutes the O antigens which are important virulence factors that are targets of both the innate and adaptive immune systems and play a major role in host-pathogen interactions. O antigens are responsible for antigenic specificity of the strain and determine the O serogroup. The designation of O serogroups is important for classifying E. coli strains, for epidemiological studies, in tracing the source of outbreaks of gastrointestinal or other illness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 116 publications
1
75
0
1
Order By: Relevance
“…Cell wall and membrane envelope metabolism accounted for 18% of reactions in the pan reactome. These reactions account for a major phenotypic distinction between E. coli strain's serogroup, in particular the O antigen (20). Also, 30% of amino acid metabolism reactions are part of the pan reactome.…”
Section: Resultsmentioning
confidence: 99%
“…Cell wall and membrane envelope metabolism accounted for 18% of reactions in the pan reactome. These reactions account for a major phenotypic distinction between E. coli strain's serogroup, in particular the O antigen (20). Also, 30% of amino acid metabolism reactions are part of the pan reactome.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the identification of strains of the same O serogroup is essential in outbreak investigations and surveillance. Many rapid and lowcost genetic methodologies for identifying E. coli O serogroups have been developed (10)(11)(12)(13)(14)(15). Coimbra et al (11) reported a broad O-typing method characterized by the restriction fragment length polymorphism pattern of amplified O-antigen biosynthesis gene clusters (O-AGCs).…”
mentioning
confidence: 99%
“…On the other hand, in most cases, these target sequences of O-antigen processing genes such as wzx (encoding the O-antigen flippase), wzy (encoding the O-antigen polymerase), and the wzm and wzt genes (encoding components of the ABC transporter pathway). These are highly variable orthologs and are considered to be specific to each O serogroup (12).…”
mentioning
confidence: 99%
“…Serotyping is widely used and is a well-established type of E. coli classification for pathogenicity detection and epidemiological studies Scheutz et al, 2004). Serotyping based on the O and H antigens are considered the 'gold-standard' as only limited laboratories have the ability to type the K-group (DebRoy et al, 2011).…”
Section: Serological Classificationmentioning
confidence: 99%